Status Concerns and the Schooling Decision - Alessa Kristin Schottke; Christian Siemering (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We investigate the influence of status concerns on educational attainment and the labor market. Status is considered as the relative position in society, positively differentiated by comparison with others. We find that the perception of higher social status coming along with higher education may increase the demand for educational credentials. In turn, we can observe a positive effect on labor supply of higher educated people, affecting their wage rate in a negative way. Moreover, the wage for less educated people increases after the introduction of social status due to the low employment rate.
Keywords: J31; Z13; D03; 330